Sustainable Agriculture and Green Economy: A Synergy for SDG 2 and SDG 13 - Umaira, Triana; Fajrian, Ade (PT. Civil Military Center, 2025)
Sustainable agriculture and the green economy play a crucial role in achieving Sustainable Development Goal (SDG) 2: